High-voltage engineering and testing - Ryan, H. M. (Hugh McLaren) (The Institution of Engineering and Technology, 2013)
This third edition comprises 23 chapters covering high-voltage engineering and testing themes - with many valuable references describing CIGRE work. This new third edition of HVET will again provide a valuable broad overview of the developments in the sector including renewable energy (windfarms, biomass etc.). Cost, environmental and operational aspects are covered. Modern substation condition monitoring strategies for switchgear, transformers and cables are discussed and new insulation co-ordination (IC) technologies are discussed - adopted using higher performance arresters for new ultra high-voltage AC transmission substations in China, India and Japan (operating at voltages >=1,100 Kv). Fundamental design concepts, special strategic network developments, asset management issues at EHV and other special matters are also discussed. The book also touches on how network equipment and systems operate and are monitored and managed at this time - and can perhaps best be managed in the future.